Hollywoodfilmtitel im Deutschen und im Thailändischen - Attaviriyanupap, Korakoch; Seenlabut, Pasinee (Linguistik Online, 2020)
This paper is a contrastive analysis which explores how the English Hollywood film titles are translated into German and Thai. The purpose of the study is to answer the following questions: 1) What is the difference between the length of the film titles in the original English version and in their German and Thai translation; 2) Which translation methods can be found in the translation of the Hollywood film titles into German and Thai?; 3) Which constructions can be found in the translated film titles in German and in Thai in comparison to the original ones? The study is based on a corpus of 900 film titles including 300 of Hollywood film titles and their translation in German and Thai. It is found that the length of the film titles is between one and twelve words. While film titles in both European languages contain mostly two words, the use of four-word titles occurs most frequently in the Thai translation. 10 translation strategies are found in total. In German, the original English titles are mostly kept. In contrast to German, the titles are mostly totally changed in Thai. Regarding the structure of the film titles, there are totally 7 categories. Nominal phrase is the most frequently found construction of film titles in all these three analyzed languages.